2005
DOI: 10.1002/pola.20583
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations of polypropylene glycol (PPG) and isophorone diisocyanate (IPDI)‐based polyurethane prepolymer by 1D and 2D NMR spectroscopy

Abstract: Polyurethane prepolymers are widely used in reactive hot melt adhesives and moisture cured coatings. NCO-terminated polyurethane of polypropylene glycol (PPG)-1000 and isophoron diisocyanate (IPDI) with an NCO/OH ratio of 1.2:1 were prepared without any catalyst or solvent. 1D and 2D NMR spectroscopy was used for the structural investigation of the synthesized prepolymer. 1 H NMR spectra and dibutylamine back-titration were used to monitor the reaction of isocyanate groups with the hydroxyl function of PPG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 21 publications
3
84
0
Order By: Relevance
“…The resonance peaks of the À ÀNHÀ ÀCOOÀ À protons of all of the PUs appeared in the region 9.91-9.94 ppm, except for those of IPDI and HDI-based polymers. In IPDI and HDI-based PUs, À ÀNHÀ ÀCOOÀ À protons are also observed around 5.55-5.75 ppm, which are in conformity with an earlier report, 19 but in the monomer, À ÀOH protons are found around 9.93 ppm.…”
Section: Spectral Datasupporting
confidence: 90%
“…The resonance peaks of the À ÀNHÀ ÀCOOÀ À protons of all of the PUs appeared in the region 9.91-9.94 ppm, except for those of IPDI and HDI-based polymers. In IPDI and HDI-based PUs, À ÀNHÀ ÀCOOÀ À protons are also observed around 5.55-5.75 ppm, which are in conformity with an earlier report, 19 but in the monomer, À ÀOH protons are found around 9.93 ppm.…”
Section: Spectral Datasupporting
confidence: 90%
“…As the reaction was carried out for 6 h in the absence of any added catalyst, so the product mixture contains diurethane, monourethane and unreacted diisocyanate. In our earlier paper [24], the structural assignments of different protons and carbons associated with different environment in the liquid state were carried out by 1D and 2D homo and hetero-nuclear nuclear magnetic resonance (NMR) experiments, and have shown that after 6 h of reaction the fractional isocyanate conversion was approximately 10-15% for IPDI based formulation. The % NCO conversion for TDI based system showed 35-40% after 6 h as determined by dibutylamine titration.…”
Section: Methodsmentioning
confidence: 99%
“…1 Structures of both the diols and PUs were characterized with FTIR and NMR. FTIR spectra indicate the disappearance of bands due to both hydroxyl (at 3390 and 3402 cm 21 ) and isocyanate (at 2268 cm 21 ) groups, but they exhibit several characteristic stretching vibrations due to NÀ ÀH, C¼ ¼O, CH¼ ¼N, and CÀ ÀH moieties. Hydrogen bonding in PUs is of great interest because it is important 18 in determining the phase segregation.…”
Section: Solubilitymentioning
confidence: 98%